Impact of climate-smart agriculture adoption on food security and multidimensional poverty of rural farm households in the Central Rift Valley of Ethiopia - Ali, H.; Menza, M.; Hagos, Fitsum; Haileslassie, Amare (Springer, 2022)
Background: Climate change has perverse efects on the natural resource base and agricultural productivity, negatively afecting the well-being of households and communities. There are various attempts by the government and NGOs to promote climate-smart agricultural (CSA) practices to help farmers adapt to and mitigate these negative impacts. This study aimed to identify CSA practices widely adopted in the study area and examined their impacts on rural farm households’ food security and multidimensional poverty. A three-stage proportional to size sampling procedure was followed to select four districts out of nine districts, and 278 households were randomly selected from two kebeles from each district. A cross-sectional data of the 2020–2021 cropping season were collected using a structured and pretested survey questionnaire. The food consumption score, dietary diversity score, food insecurity experience scale, and multidimensional poverty index, constructed out of 9 indicators, were used to assess households’ food security and poverty status, respectively. A multinomial endogenous switching regression model was used to assess average treatment efects on these outcome indicators. Results: Widely adopted CSA practices are conservation agriculture, soil fertility management, crop diversifcation, and small-scale irrigation. The results illustrated that adopter households on average showed more food consumption score, dietary diversity score, and less food insecurity experience scale than non-adopters. The results also showed that CSA adopter households, on average, have a low deprivation score in multidimensional poverty than non-adopter households. Accelerating wider adoption of CSA through up-scaling incentives is quite important. Conclusion: This study showed that CSA adoption improves households’ food security and reduces multidimensional poverty. We conclude that up-scaling of CSA practices is important for contributing to the achievement of SDG1, SDG2 and SDG13 targets.